Genetic Factors in Mental Health Disorders in adolescents in West Java: Experiencing it with Genomics - Anurogo, Dito; Muhtadi, Muhamad Ammar; Farooq Mujahid, Muhammad Umer (Westscience Press, 2023)
Mental health disorders among adolescents in West Java have become a growing concern, impacting their well-being and future prospects. This study aimed to investigate the genetic factors contributing to these disorders, utilizing genomic analysis and qualitative exploration of lived experiences. A mixed-methods approach was employed, including quantitative surveys, genomic analysis, and qualitative interviews. The study comprised a diverse sample of adolescents from various socio-economic backgrounds and age groups in West Java. The quantitative analysis revealed a significant prevalence of mental health disorders, with approximately 35% reporting symptoms of depression and 55% meeting criteria for generalized anxiety disorder. Genomic analysis identified specific genetic markers associated with these disorders, emphasizing their genetic underpinnings. Qualitative data underscored the impact of stigma, coping mechanisms, family support, and cultural factors on adolescents' mental well-being. The findings of this study provide a comprehensive understanding of mental health in adolescents in West Java, integrating genetic and socio-cultural perspectives. The prevalence rates highlight the urgency of addressing mental health issues in this population. Genetic insights suggest opportunities for personalized interventions, while qualitative findings emphasize the importance of reducing stigma and enhancing community-based support. These findings contribute to the development of targeted interventions and policies aimed at improving the mental health of adolescents in West Java.